2022
DOI: 10.1097/mou.0000000000001066
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and kidney stones: cause and effect?

Abstract: Purpose of reviewThis short review is intended to highlight the potential role of inflammation as a key pathological driver, rather than a mere consequence, of nephrolithiasis. Although there is clearly a strong likelihood that the relationship is bidirectional, and that kidney stone-triggered inflammation can establish a vicious cycle of tissue injury and stone formation. Recent findingsThese consist of data from both recent preclinical and clinical studies demonstrating the importance of inflammation in mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…A variety of processes including supersaturation of urinary stone components, reduction of inhibitors of stone formation (Cicerello et al, 2019 ), and renal tubular epithelial cell injury (Aggarwal et al, 2013 ) are involved. Metabolism and inflammation are considered important factors involved in the formation of renal stones (Tian et al, 2022 ; Capolongo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of processes including supersaturation of urinary stone components, reduction of inhibitors of stone formation (Cicerello et al, 2019 ), and renal tubular epithelial cell injury (Aggarwal et al, 2013 ) are involved. Metabolism and inflammation are considered important factors involved in the formation of renal stones (Tian et al, 2022 ; Capolongo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that renal stones can cause inflammation, which can in turn lead to stone recurrence. In this way, a toxic cycle of kidney tissue injury and recurrent stone formation ensues [ 12 ]. Kidney stones can cause oxidative stress and trigger an inflammatory response with the release of pro-inflammatory cytokines like IL-1β and IL18 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal papilla specimens from patients with RPs exhibit extensive cell damage and interstitial fibrosis surrounding the crystal blockages, with the stone matrix containing inflammation‐related proteins 40,81 . Basic studies examining renal epithelial cell responses to high concentration of oxalate or CaOx crystals and animal models of hyperoxaluria‐induced CaOx crystal deposition have further highlighted the importance of oxidative stress and inflammation 82–84 . Overwhelming oxidative stress and inflammatory responses can lead to the expression of molecules involved in crystal binding, disruption of tight junctions, injury, cell death and shedding in RTECs 77,82 .…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
“… 40 , 81 Basic studies examining renal epithelial cell responses to high concentration of oxalate or CaOx crystals and animal models of hyperoxaluria‐induced CaOx crystal deposition have further highlighted the importance of oxidative stress and inflammation. 82 , 83 , 84 Overwhelming oxidative stress and inflammatory responses can lead to the expression of molecules involved in crystal binding, disruption of tight junctions, injury, cell death and shedding in RTECs. 77 , 82 Additionally, oxidative stress and inflammation mediate the polarization of macrophages, collagen mineralization, macrophage‐mediated stone clearance, interstitial fibrosis and the formation of RPs in the kidney interstitium.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%